2016
DOI: 10.1111/psyp.12651
|View full text |Cite
|
Sign up to set email alerts
|

Goal relevance influences performance monitoring at the level of the FRN and P3 components

Abstract: The Feedback-Related Negativity (FRN) provides a reliable ERP marker of performance monitoring (PM). It is usually larger for negative compared to positive feedback, and for unexpected relative to expected feedback. In two experiments, we assessed whether these effects could be modulated by goal relevance, defined as feedback informativeness (reliability) and/or impact on a person's goals. 64-channels EEG was recorded while 30 participants (in each experiment) performed a speeded Go/NoGo task across blocks in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
84
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(99 citation statements)
references
References 54 publications
12
84
3
Order By: Relevance
“…However, this result was not unexpected, but very much in line with previous ERP studies using the same speeded Go/NoGo task with a very strict time pressure and updated RT deadline (Vocat et al, 2008). These conditions necessarily increased uncertainty at the time of key press given that performance was based on both accuracy and speed (Walentowska et al, 2016). As a matter of fact, (enhanced) uncertainty also increases the CRN component (Coles et al, 2001;Falkenstein et al, 2000;Gehring et al, 1993).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, this result was not unexpected, but very much in line with previous ERP studies using the same speeded Go/NoGo task with a very strict time pressure and updated RT deadline (Vocat et al, 2008). These conditions necessarily increased uncertainty at the time of key press given that performance was based on both accuracy and speed (Walentowska et al, 2016). As a matter of fact, (enhanced) uncertainty also increases the CRN component (Coles et al, 2001;Falkenstein et al, 2000;Gehring et al, 1993).…”
Section: Discussionsupporting
confidence: 89%
“…Noteworthy, the lack of group differences at the behavioral level (speed and accuracy) was not odd in the present case, but expected given the specifics of the Go/NoGo task used. Since the RT deadline was calibrated and updated at the single subject level, it inevitably led to a comparable number of response errors (and balanced speed) between the two groups, as already reported in previous studies using the same task and between-subjects experimental design (see Aarts & Pourtois, 2010;Aarts et al, 2013;Koban, Brass, Lynn, & Pourtois, 2012;Rigoni, Pourtois, & Brass, 2015;Walentowska, Moors, Paul, & Pourtois, 2016).…”
Section: Discussionmentioning
confidence: 78%
“…Relevant to the current study, the difference between happy and angry expressions was examined. In this regard, the previous studies showed larger EPN59, larger P3b and SPW59 for angry faces than for happy faces, but smaller N2 for angry faces than for happy faces when faces were presented in a trust-varied context73. For conciseness, following previous studies3258, the current study merged the analysis on FRN and N2, and the analysis on feedback-related P300 and P3b, given that the FRN is a special instance of the N2 component74757677 and the feedback-related P300 belongs to P300 family40414243.…”
mentioning
confidence: 78%
“…The extracted average waveforms for each participant and condition were used to calculate grand-average waveforms. For statistical analyses, three different clusters of scalp sites were formed to evaluate the components peaking in different regions59: fronto-central (electrodes: F1, Fz, F2, FC1, FCz, FC2, FCz, C1, Cz, C2), occipito-temporal (left: TP7, P7, PO7, and right: TP8, P8, PO8), and parietal (P1, Pz, P2, PO3, POz, PO4). Then, based on the inspection of visual peaks for the current data, the mean amplitude in the fronto-central cluster was calculated for the interval between 180 and 220 ms for the VPP, between 220 and 280 ms for the N2/FRN, and between 600 and 800 ms for the SPW.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation